Genetic Programming 14th European Conference, EuroGP 2011, Torino, Italy, April 27-29, 2011. Proceedings - Silva, Sara.; Foster, James A.; Nicolau, Miguel; Machado, Penousal; Giacobini, Mario; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 14th European Conference on Genetic Programming, EuroGP 2011, held in Torino, Italy, in April 2011 co-located with the Evo* 2011 events. This 20 revised full papers presented together with 9 poster papers were carefully reviewed and selected from 59 submissions. The wide range of topics in this volume reflect the current state of research in the field, including representations, theory, novel operators and techniques, self organization, and applications.
Keywords: Computer science; Computer software; Artificial intelligence; Optical pattern recognition; Bioinformatics; Computer Science; Programming Techniques; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Pattern Recognition; Artificial Intelligence (incl. Robotics).; Computational Biology/Bioinformatics.